PENGARUH DIGITAL CYBER CITIZENSHIP TERHADAP PERILAKU BULLYING DI KALANGAN REMAJA - Farida; Latifah Puji Lestari; Alda Shafira; Diana Fisa Astuti; Nika Christina; Afandi (Nusantara Hasana Journal, 2023)
This article aims to determine the effect of digital cyber citizenship on bullying behavior among adolescents. Based on the results of Kominfo's research, it is stated that Indonesian children and adolescents use digital media and internet access in their daily lives but there is a lack of parental supervision which can have a negative impact on adolescent behavior. The emergence of juvenile delinquency due to information obtained through internet digital media that is not suitable for consumption, will encourage the emergence of deviant behavior in children and adolescents such as acts of bullying (bullying), a culture of insulting and cursing which is often carried out through internet media, especially social media, such as Facebook. , Instagram, Twitter and so on. This study uses a qualitative approach and study of literature, which basically will determine the effect of digital cyber citizenship on bullying behavior among adolescents. Qualitative research is used to explore and understand individuals and groups that are considered to be part of a social problem. Usually data is analyzed from general to specific matters taken from collecting data from informants, then the data is collected and then translated into scientific language. From some of the research results that have been found that cyber bullying is very common, there are still many Indonesian people who still have low self-awareness so they consider it a natural thing so that more education is needed about the impact of cyber bullying so that people don't make it a waste.